EFEKTIVITAS REKRUTMEN DALAM KINERJA KARYAWAN PADA BAGIAN PEMASARAN DI CV IKRA CENDANA LINTANG JAKARTA - Rosento RST (Universitas Bina Sarana Informatika, 2018)
ABSTRACT Human Resources has a very important role in developing and achieving the goals of the organization, in addition to organizational performance is also based on the human factor. In order to obtain reliable and professional staff, good activities are required, including recruitment and selection process in the early stages. Good recruitment and selection activities are expected to produce well-performing candidates. To form a qualified workforce it is necessary to determine the qualifications of the required workforce and place it in the right position, so that the company's goals will be achieved. To achieve the goals of the company then required a good workforce planning for each division or department within the company. With the existence of manpower planning, it is expected the company will obtain information relating to the determination of the quality of labor required by the company to fill the existing positions effectively. Related to this matter, CV. Ikra Cendana Lintang will be able to compete with other similar companies in Indonesia, of course, also require a careful and precise manpower planning in order to remain able to carry out its activities well.Keywords: Recruitment, Employee Performance